Determination of peak- to-total ratio versus gamma-ray energy of a HPGe detector - Supian Samat; Lee , Yuen Kong (Universiti Kebangsaan Malaysia, 2006)
This note describes a method for the determination of the peak-to-total ratio, P/T versus gamma-ray energy of range 59.54-1836.03 keV of a HPGe detector. Results show that this ratio decreases with energy. To check the validity of these results, two approaches of results comparison, namely with the ratio reported by Cesana and Terrani in year 1989 and with the shape of total efficiency reported by Debertin and Helmer in year 1988 were taken. lt is shown that this method gives satisfactory results since the obtained values of P/T and the shape of the total efficiency curve were in good agreement with the reported works. The precautional step that need to be taken when dealing with energy 59.54 keV 241Am source and the reason for taking the total efficiency as the evaluation tool are given.